(untitled) (Hungarian Journal of Industry and Chemistry, 2010)
It is important to know the main characteristics of production geometry of the hob for the precise and appropriate quality production, since the various cog wheels, worm gears are produced with this tool. The hobs have complicated geometry and are expensive tools so the production is very expensive.